2003
DOI: 10.1002/bit.10724
|View full text |Cite
|
Sign up to set email alerts
|

Modeling chromate reduction in Shewanella oneidensis MR‐1: Development of a novel dual‐enzyme kinetic model

Abstract: Chromate (Cr(VI)) reduction tests were performed with nitrate- and fumarate-grown stationary phase cultures of Shewanella oneidensis MR-1 (henceforth referred to as MR-1) and disappearance of Cr(VI) was monitored over time. A rapid initial decrease in Cr(VI) concentration was observed, which was followed by a slower, steady decrease. These observations appear to be consistent with our previous results indicating that Cr(VI) reduction in MR-1 involves at least two mechanisms (Viamajala et al., 2002b). Modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 47 publications
(73 reference statements)
5
37
0
Order By: Relevance
“…2). The specific rate of nitrate reduction Pantoea agglomerans SP1 [7] 1.87*10 À10 a Assuming that 1 g dry-cell weight is approximately 7.3*10 12 cells [33] at log-phase was about 3.5 times higher in the absence of chromate (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The specific rate of nitrate reduction Pantoea agglomerans SP1 [7] 1.87*10 À10 a Assuming that 1 g dry-cell weight is approximately 7.3*10 12 cells [33] at log-phase was about 3.5 times higher in the absence of chromate (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…It had been suggested that the interaction of nitrite with chromate can result in chemical chromate reduction associated with nitrite oxidation [19]. Then again, other authors [33] using a fixed initial Cr(VI) concentration of 0.04 mmol and varying the nitrite concentration in the range of 0-2 mmol have reported the inhibition of specific rates of Cr(VI) reduction with nitrite for Shewanella oneidensis MR-1. However, according to our experiments, this effect is only affiliated with their specific strain.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, reduction of Cr(VI) to Cr(III) is a fundamental goal of many Cr(VI) remediation strategies (Lovley and Anderson 2000;Khan and Puls 2003;Alowitz and Scherer 2002;Melitas et al 2001) and the ability of metal reducing microorganisms to catalyze this reduction has been the subject of extensive research (Sani et al 2002;Guha et al 2001;Liu et al 2002;Viamajala et al 2003;Wielinga et al 2001;Viera et al 2003). While many examples of bacterial Cr(VI) reduction have been reported, virtually all were conducted at near-neutral pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to reduce insoluble metals such as Fe(III) and Mn(III/IV) at neutral pH in oxidizing environments, this network must be able to transfer electrons from the cytoplasmic membrane where electrons are generated to the extracellular surface of the outer membrane, where reduction is thought to occur (27). Identification of the proteins and their functions in mediating metal reduction is of considerable importance both from a standpoint of understanding bacterial physiology and in order to facilitate bioremediation of contaminated sites, since these metal-reducing activities may also function in the reduction and immobilization of toxic metals, including U(VI), Tc(VII), and Cr(VI) (25,(36)(37)(38)(39)(40).…”
mentioning
confidence: 99%